Metode Pembelajaran Cooperative Learning Script dalam Pembelajaran Keterampilan Menyimak Kelas X SMA Islam Darun Najah - wasi'ah, wasi'ah (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
Listening comprehension is one of the fundamental aspects in the development of language skills. Through effective listening learning, students can enhance their ability to understand and interpret verbal messages more effectively. The use of the cooperative learning script method in the classroom learning process can address the issues that arise during the learning process. This method trains students to be confident when presenting in front of the class. This cooperative learning script method can also be used by teachers to assess students' understanding of listening skills learning. This research uses a qualitative approach with a descriptive type. The respondents of this research are tenth-grade students of Darun Najah Islamic High School. The data collection techniques in this study use observation, questionnaires, interviews, and documentation. The research results indicate that the cooperative learning script method can be used as a method in listening instruction, particularly for the material of folk tales. This cooperative learning script method can assist teachers in delivering the material of folk tales during the learning process. The cooperative learning script method can have a positive impact on listening skills development. In addition, the cooperative learning method has become an interesting way to boost students' enthusiasm for learning in the classroom.